ANALISIS KELEMBAGAAN PENYULUHAN PERTANIAN DI KABUPATEN KAMPAR - Widya Dwi Pertiwi Pelawi; Rosnita Rosnita; Roza Yulida (Fakultas Pertanian, Universitas Riau, 2017)
Institutional extension is a government agency which has the task and function of organizing counseling. The enactment of the Constitution No. 32 of 2004 explained that the extension activities carried out in their respective offices and constitution No 16 of 2006 explaining there are special institutions cause a wide range of extension activities in each area. The objectives of this research were reviewing the vision and mission of extension agents, analyzing the role and function of the structure based on each institution, reviewing the policy rule extension, and reviewing each program of extension agency. The research was conducted at BPPKP in Kampar District. The number of respondents were 23 people. They are heads of the field extension and head of the hall extension. The data used were primary and secondary data. Primary data was collected through interview method. Data analysis applied descriptive method. The results showed that mission and vision led to the development of natural resources and human resources, the role functions and duties of each structure has not been fully implemented in accordance with policy rules and extension activities have not been operating effectively and efficiently, rules defined policy has not done well in which BPPKP has not fully guided by the Constitution No. 16 of 2006 and extension activities are not polyvalent, programs were prepared based on the needs of farmers.